Substituted 2,5 thiophene dicarboxaldehyde bisthiosemicarbazones and their copper(II) complexes: Synthesis, structure elucidation, HSA binding, biological activities and docking studies - Ul Ain, Qurat; Singh, Iqubal; Carmieli, Raanan; Savci, Ahmet; Paul, Kamaldeep; Sharma, Rekha (Elsevier, 2023)
Reaction of copper (II) acetate with 2,5 thiophenedicarboxaldehyde bisthiosemicarbazone (2,5 H2bttsc, 1H2L), 2,5 thiophenedicarboxaldehyde-N1-methyl bisthiosemicarbazone (2,5 H2bttsc-N1-Me, 2H2L) and 2,5 thiophenedicarboxaldehyde -N1-phenyl bisthiosemicarbazone (2,5 H2bttsc-N1-Ph, 3H2L) in 1:1 (M:L) molar ratio yielded complexes of stoichiometry, [Cu(L)] 1-3 (1L, 1; 2L 2; 3L 3). All the complexes are characterized using elemental analysis FTIR, Mass and ESR spectroscopy. The two distinct g values, g

= 2.40 (1), 2.15 (2), 2.20 (3) and g & BOTTOM; = 2.08 (1), 2.07 (2), 2.12 (3) indicate axial symmetry for the complexes. The greater g

value than g & BOTTOM;, confirms the presence of free electrons in dx2-y2 ground term in square planar geometry. The ligands (1H2L - 3H2L) and their complexes (1-3) were tested for DPPH radical scavenging, ABTS radical scavenging, FRAP ferric reducing, and CUPRAC cupric reducing antioxidant capacity assays. In general, all the ligands and their metal complexes exhibited moderate antioxidant potential, however 3H2L has shown best Cu2+ reducing activity (7.34 & mu;g TE/ml) and ABTS radicals scavenging activity (IC50, 16.95) amongst all. Ligands (1H2L - 3H2L) and their complexes (1-3) were also evaluated for anti-tuberculosis activity against M. tuberculosis H37RV strain. It has been observed that with the increase of hydrophobicity of ligand due to substituent present at N1 atom, anti-TB activity increased (H, MIC = 6.25 & mu;g/ml < Me, MIC = 3.12 & mu;g/ml < Ph, MIC = 1.6 & mu;g/ml). Molecular modeling studies have shown considerable intermolecular interaction of these compounds with minimum binding energy -5.8 (1H2L), -5.8 (2H2L), -9.6 (3H2L), -6.9 (1), -6.6 (2) and -9.6 (3) Kcal/ mol, which also supports the experimental data. Pharmacokinetics (effective transport of molecule to their target sites) was studied using drug-protein binding study of molecules with human serum albumin (HSA) was performed using UV-vis and fluorescence spectroscopy. The ligand 2H2L and complex 2 showed strong binding interactions with HSA having binding constant values of 4.24 x 105 M-1 and 4.92 x 105 M-1 respectively.
Keywords: Bisthiosemicarbazones; Copper (Ii) Complexes; Anti -Tubercular Activity; Molecular Docking; Antioxidant Activity; Spectroscopy; Human Serum-Albumin; Electronic-Properties; Antioxidant Capacity; Molecular Docking; Cu-Atsm; Thiosemicarbazones; Bis(Thiosemicarbazone); Nickel(Ii); Bovine; Redox